Kvantni internet - Hočevar, Matic (Matrika, 2024)
Quantum communication is a field of study that focuses on the transmission of quantum information. For this, a quantum internet network is required. This article presents the quantum mechanical phenomena on which the quantum internet is based and the components of the quantum internet network.
Keywords: kvantna komunikacija; kvantne informacije; kvantni internet; quantum communication; quantum information; quantum internet